A comparison of radiation doses to selected vital organs in the maxillo-facial region using three different settings on the Galileos CBCT machine housed in the Wits Dental Hospital - Dimtchev, Dimcho Lubomirov (My University, 2015)
A comparison of radiation doses to selected vital organs in the maxillo-facial region at three different settings on the Galileos cone-beam computed tomography (CBCT) machine in the Wits Dental Hospital, was conducted with the courtesy of the Department of Medical Physics of the Charlotte Maxeke Johannesburg Academic Hospital. The study made use of the RANDO phantom and TLD- 100 detector chips, which provided detailed mapping of the dose distribution from the Galileos CBCT machine. Sixty-two Sanford® lithium fluoride dosimeters- (TLD- 100) were irradiated using a calibrated known x-ray source after having undergone a recommended annealing cycle. The data showed great consistency in the results. Association between the different imaging modalities was further investigated using Kruskal-Wallis equality-of-populations rank test and Chi-squared test. A p-value of <0.05 was considered statistically significant. Since there do not appear to be major differences between the radiation doses for the different settings of the Galileos CBCT machine, the author recommends the use of the combined setting at all times for optimum image quality.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfillment of the requirements for the degree of MSc (Dent)
Keywords: Radiation Dosage; Dose-Response Relationship, Radiation